Multiplicity dependence of jet-like two-particle correlation structures in p-Pb collisions at √sNN=5.02 TeV - Abelev, Betty; Angelov, Venelin; Busch, Oliver; Glässel, Peter; Klein, Jochen; Leardini, Lucia; Lohner, Daniel; Lu, Xianguo; Maire, Antonin; Oyama, Ken; Pachmayer, Yvonne C.; Reygers, Klaus; et al. (Physics letters, 2015)
Two-particle angular correlations between unidentified charged trigger and associated particles are measured by the ALICE detector in p–Pb collisions at a nucleon–nucleon centre-of-mass energy of 5.02 TeV. The transverse-momentum range is examined, to include correlations induced by jets originating from low momentum-transfer scatterings (minijets). The correlations expressed as associated yield per trigger particle are obtained in the pseudorapidity range . The near-side long-range pseudorapidity correlations observed in high-multiplicity p–Pb collisions are subtracted from both near-side short-range and away-side correlations in order to remove the non-jet-like components. The yields in the jet-like peaks are found to be invariant with event multiplicity with the exception of events with low multiplicity. This invariance is consistent with the particles being produced via the incoherent fragmentation of multiple parton–parton scatterings, while the yield related to the previously observed ridge structures is not jet-related. The number of uncorrelated sources of particle production is found to increase linearly with multiplicity, suggesting no saturation of the number of multi-parton interactions even in the highest multiplicity p–Pb collisions. Further, the number scales only in the intermediate multiplicity region with the number of binary nucleon–nucleon collisions estimated with a Glauber Monte-Carlo simulation.
Available online 20 November 2014
*ALICE Collaboration: B. Abelev, V. Anguelov, O. Busch, P. Glaessel, J. Klein, L. Leardini, D. Lohner, X.G. Lu, A. Maire, K. Oyama, Y. Pachmayer, K. Reygers, R. Schicker, J. Stachel, J. Stiller, M.A. Voelkl, B. Windelband, M. Winn, A. Zimmermann [und 926 weitere Personen]
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
Gesehen am 16.07.2021